Entomotoxicity of ZnO NPs synthesized using Clausena anisata Hook.f. ex Benth(ulmaayii) leaf extract against maize weevil, Sitophilus zeamais Mostch (Coleoptera: Curculionidae) - Gindaba, Adugna; Negeri, Mulugeta; Saka, Abel (Journal of Phytology, 2023)
The application of leaf extract to synthesize nanoparticles has been taken as a green method. In this study, the potential for synthesizing zinc oxide nanoparticles (ZnO NPs) from Clausena anisata Hook.f. ex Benth. leaf extract was investigated. The source of zinc was zinc nitrate hexahydrate (Zn(NO3)2.6H2O). The characterization study was done by Ultraviolet–visible (UV-Vis) spectroscopy, X-ray diffraction (XRD), scanning electron microscope (SEM), Transmission electron microscope (TEM) and atomic force microscopy (AFM). The crystalline shape of nanoparticles is disclosed inside the XRD result, morphology is confirmed through SEM effects, and consequently, the ZnO NPs scale was predicted. ZnO NPs were synthesized to work against Sitophilus zeamais adults. A mortality count was carried out in 14 days and all the 3 dosages (0.2 g, 0.4 g and 0.6 g) were effective in killing S. zeamais. F1 progeny emergence was highly reduced in comparison to untreated control. Maize seeds were successfully germinated after treatment application with ZnO NPs.